Tarde and Schumpeter: A Similar Vision - Taymans, A. C. (Quarterly Journal of Economics, 1950)
I. A social theory in Schumpeterian terms, 611. — II. Objections to the claim of similarity of vision, 612. — III. Invention versus innovation, 614. — IV. The "directing forces, " 616. — V. Description of the business cycle, 621.